Eficiencia de las máquinas incubadoras nacedoras, CASP y CHICK MASTER, en los parámetros de incubabilidad de huevos de gallinas reproductoras pesadas de la línea COBB AVIAN 48. - Yauricasa Vergaray, Sofia Edita (2012)
The present investigation was realized in The Incubative plant MERCOA VES S.A.C, with the purpose to determining the efficiency of incubator- hatcher machines, Casp and Chick Master, in the parameters hatchability of eggs from reproductive· heavy hens ofthe Cobb Avian line 48. We used 27648 eggs hatching position 4 ages (35- 37, 39-43,49-52 and 54-56 weeks) and two treatments (Tl:Casp and T2: Chick Master) with a design BCA. The percent of fertility showed significant differences between treatments (p <0.05), obtaining T2: 91.76% and Tl: 91.04%. The highest percent (83.21%) ofhatchabilitywas awarded to the Tl, and T2 was 80.40%. For the loss ofhumidity, the minar percent was obtained with the T 1: 11.99%, while the T2 was 13.12%. F or mortality rates found no significant differences (p >0.05) between treatments. The T1 was the highest percent ofthe total birth and birth on fertile (84.02 and 92.17%, respectively). The greater weight and performance in chicken was obtained with the T1 (46.85 g, 69.35%, respectively), while the T2 obtained: 45.80 g and 67.85% respectively. The two treatments have differences between them, smce most of the evaluated variables showed highly significant differences (p <0.01). The lower cost to reach a chicken to incubation was obtained by Tl: S/. 0.049. It is concluded that the Tl is more efficient owed to that you obtain the bigger productive and cost-reducing benefits.